Analisis Retorika Pidato Presiden Jokowi di Ibu Kota Nusantara (IKN) pada Kanal Youtube Official iNews - Atef Fahrudin; Diding Bajuri; Syamsul Arif Billah (Universitas Majalengka, 2022)
This research was made to analyze the rhetoric of President Jokowi's speech at the IKN on the iNews Official Youtube Channel. The method used in this study is descriptive qualitative through an interpretive paradigm. The data collection technique used is watch, listen and note. Then it is analyzed by interpreting Aristotle's rhetorical concept. The results of this study show that the speech delivered by President Jokowi belongs to the type of deliberative (political) rhetoric, namely rhetoric whose content is in the form of calls and prohibitions which are usually carried out by leaders such as the president or regional heads when setting policies and oriented to the future. These results are evidenced by the findings of 9 data related to the type of deliberative (political) rhetoric. The speech delivered by President Jokowi also fulfilled the elements of a rhetorical triangle. This is because based on the results of research on Jokowi's speech there is ethos (credibility), where Mr. Jokowi as the person delivering the speech has the status of president and forestry person, and contains elements of phatos (emotions) and logos (logical evidence) in it. President Jokowi's speech also fulfilled the five canons of rhetoric, namely five rhetorical principles: (1) inventio (invention); (2) disposition (arrangement); (3) elocutio (style); (4) actio (delivery) and memoria (memory). These results are evidenced by the findings of 25 data related to rhetorical principles.